GRID INTERACTIVE SOLAR PV BASED WATER PUMPING SYSTEM - Ummi Hani; S Rajesh; Raviteja B; M Sageer Ahmed; S MD Asif (International Educational Journal of Science and Engineering, 2026)
The integration of grid-interactive solar photovoltaic technology with water pumping systems provides a sustainable and efficient solution for agricultural irrigation and rural water management. The proposed system prioritizes solar energy for water pumping while interacting with the utility grid for backup and surplus energy export. The system uses solar PV panels, MPPT controllers, inverters, sensors, and BLDC motors for efficient operation. The use of BLDC motors improves efficiency, reliability, and operational lifespan compared to conventional motors. Intelligent controllers and monitoring systems ensure uninterrupted and optimized operation under varying environmental conditions. The proposed system reduces electricity consumption, minimizes dependence on diesel generators, and supports sustainable agricultural practices.